IMPLEMENTASI PROGRAM PEMBEBASAN SANKSI PAJAK KENDARAAN BERMOTOR DALAM MENUMBUHKAN KESADARAN DAN KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR: Studi Kasus Samsat Kabupaten Purworejo - Jatmiko Ariseto (STIE Rajawali Purworejo, 2022)
The aim of this research is the need for a study and evaluation to determine the implementation of the motor vehicle tax sanction exemption program, supporting programs other than motor vehicle tax sanction exemption and how the motor vehicle tax sanction exemption program increases public awareness and compliance in paying taxes, so that income from the tax sector motorized vehicles can achieve the value targeted by the Provincial Government. This research uses a descriptive qualitative method by determining sources using purposive sampling techniques, namely decisions taken by research about who needs to be interviewed, when to make observations, or what documents or how many documents need to be studied. The data collection methods used were interviews, documentation, literature study and observation. This research uses data analysis according to Miles and Huberman where the stages are data reduction, data presentation, and drawing conclusions. The results of the research show that the policy in Governor Regulation (Pergub) Number 25 of 2021 dated 06 May 2021 concerning the motor vehicle tax sanction exemption program can work. smoothly according to the expected targets and realization, and effective in increasing public compliance and awareness in paying their taxes. Through other supporting programs, namely Samsat Siaga, Mitra Putra Bangsa, and D2D (door to door). These three programs really help increase public awareness and compliance in paying their taxes. And there is a policy of deleting people's vehicle data if they do not pay taxes for 2 (years), so that taxpayers are expected to be aware and obedient to carry out their obligations to pay taxes on time.